ASSESSMENT OF THE PERFORMANCE OF ANCHOR BORROWERS PROGRAMME (ABP) BENEFICIARY AND NON-BENEFICIARY RICE FARMERS IN BADAGRY LOCAL GOVERNMENT AREA, LAGOS STATE, NIGERIA - O. L, BALOGUN; T. A., AYO-BELLO; C. F., ABASILIM; O. G., ABIMBOLA; O. J., AFODU; O. T., AKINWOLE (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
This study assessed the performance of Anchor Borrowers Programme (ABP) beneficiary and non-beneficiary rice farmers in Badagry LGA, Lagos State, Nigeria. Two-stage sampling procedure was used to elucidate information from 100 ABP and non ABP beneficiary rice farmers during 2019 planting season. Data were analysed using descriptive statistics, budgeting analysis and Probit regression model. Results reveal that rice farming was dominated by male farmers with average age 47.2±6.2 years. Also, the percentage of ABP beneficiaries was skewed towards the male farmers, while the inclusion of younger and youthful farmers in the programme was marginal. The mean household size of farmers was 7.2±2.6 members and most farmers (94.0%) were educated.  The average farm size was 1.99±1.44 ha while non-beneficiaries had larger farm size compared to the beneficiaries of ABP. The mean profit of the ABP beneficiary and non-beneficiary rice farmers were N631, 177.99 and N447, 092.20 respectively. This result reveals that ABP beneficiary rice farmers had a higher profit than non-beneficiaries. The result shows that the major constraint of the farmers’ participation in the programme was non-membership of cooperatives. Majority (94.2%) of the beneficiaries benefited from subsidized inputs supply.  The results of regression indicate that the extension visit, cooperative membership, gender and farm size significantly influenced farmers’ participation in Anchor Borrowers’ programme. The study recommends farmers joining cooperatives to enable them benefit from programmes channeled through groups. All stringent conditions limiting access to agricultural land should be minimized to encourage not just youth and women participation but acquisition of more land for the beneficiaries.